The UNESCO WINISIS software analysis of usage in the Philippines (1999-2005) - Ramos, Alana G.; Gonzales, Grace Marie B.; Tinao, Maria Maura S.; Faderon, Rosalie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
UNESCO developed the Computerized Documentation System/Integrated Set of Information Systems, or CDS/ISIS, which was launched and distributed for free to libraries and information centers in member countries in 1985. All in all, worldwide users could total more than 20,000. They are located mostly in the Asia-Pacific region, Africa, Latin America and the Caribbean.
In the Philippines, the Institute of Library and Information Science (ILIS) of the University of the Philippines, Diliman, has been a national distribution center since 1985. It has granted licenses to more than 1,000 institutions as of 2005. Although it has been 20 years since the ILIS started distributing the software, there has been no study undertaken with regards to the nature, breadth and scope of the user community. Actual number of installations and utilization of the software, skills training and development as well as areas for software and services enhancements.
This study hoped to fill in the data gaps. A survey, supplemented by case studies, was conducted from June to August of 2005, covering the licensee institutions in 1999 to 2005. Preliminary findings showed that:1. A WINISIS license obtained did not necessarily equal an installation. Of the 89 respondents, only 29 (33) institutions installed WINISIS and used it, while 60 did not (67).2. The free license was a definite factor in the decision to use WINISIS since most of the user institutions had limited budgets.3. WINISIS automated all major library tasks, with browsing/searching and cataloging as having the highest frequency of automation benefits.4. WINISIS features that elicited the most satisfaction in majority of user institutions were browsing capabilities and the speed of processing seraches.5. Among other users, browsing capabilities and the user interface were the features that caused the most dissatisfaction.6. A majority of the institutions (17 of 29) expressed the need for further training in WINISIS operation in the fields of: database creation and design, creating of print formats and printing.7. WINISIS is not regarded as interim software with the majority of user institutions saying that they would still be using it within the next two years.8. Among the 29 users, there was overall WINISIS user satisfaction. Sixteen institutions reported that they were satisfied with WINISIS, and six said they were not. Six other institutions had no answer.9. "Informed" librarians, with their initiative and specialized skills have the potential to convince management of the benefits of automation and influence their choice of database software.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Information services -- Philippines -- Use studies